2019
DOI: 10.3389/fimmu.2019.02762
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factor 1α Inhibits the Expression of Immunosuppressive Tryptophan-2,3-Dioxygenase in Glioblastoma

Abstract: Abnormal circulation in solid tumors results in hypoxia, which modulates both tumor intrinsic malignant properties as well as anti-tumor immune responses. Given the importance of hypoxia in glioblastoma (GBM) biology and particularly in shaping anti-tumor immunity, we analyzed which immunomodulatory genes are differentially regulated in response to hypoxia in GBM cells. Gene expression analyses identified the immunosuppressive enzyme tryptophan-2,3-dioxygenase (TDO2) as the second most downregulated gene in GB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 75 publications
2
27
0
Order By: Relevance
“…Hypoxia has been reported to promote the proliferation, migration, and invasion in prostate cancer [57]. In glioblastoma, hypoxia-inducible factor 1α inhibited the expression of tryptophan-2, 3-dioxygenase and modulates antitumor immunity [58]. Meanwhile, loss of hypoxia-inducible factor-1 in malignant epithelial cells and myeloid cells limited tumor growth [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been reported to promote the proliferation, migration, and invasion in prostate cancer [57]. In glioblastoma, hypoxia-inducible factor 1α inhibited the expression of tryptophan-2, 3-dioxygenase and modulates antitumor immunity [58]. Meanwhile, loss of hypoxia-inducible factor-1 in malignant epithelial cells and myeloid cells limited tumor growth [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to what is described above, a potential adverse effect of hypoxia on tumor-reactive T cells, has been shown; in respect of the stimulatory role mediated by HIF1-α and HIF-2α in CTL proliferation and function [ 242 ]. Mohapatra et al found that in glioblastoma (GBM) [ 243 ] there was a downregulation of immunosuppressive enzyme tryptophan-2,3-dioxygenase (TDO2) involved in tryptophan (Trp) catabolism, in a HIF1α-dependent manner, with increased T cell proliferation. While, T cell proliferation is inhibited by TDO2-expressing GBM cells under normoxia.…”
Section: The Role Of Hypoxia In Cancer Progression Metastasis Immunmentioning
confidence: 99%
“…Recent studies have demonstrated how an alternative pathway via tryptophan-2,3-dioxygenase (TDO2) is also responsible for suppressing antitumor immune response in a variety of cancers [ 207 ]. Another study has shown that HIF-1 inhibits the expression of TDO2 in glioblastoma and hypoxic conditions increase T cell proliferation [ 208 ].…”
Section: Hypoxia As An Upstream Determinant In Immune Excluded Phenotmentioning
confidence: 99%